Designing MSMEs Strategies to Survive in the New Normal Era with a SWOT-TOPSIS Approach - Masayu Rosyidah (Universitas Muhammadiyah Ponorogo, 2022)
The COVID-19 pandemic has had a significant impact on various sectors such as the healthcare system, tourism, trade, industry and economy sector especially on the economic activities of MSMEs. MSMEs are very vulnerable to being affected by business disruptions, because they are indirectly related to sectors affected by the pandemic such as the tourism sector, transportation to the culinary industry.However, in this COVID-19 pandemic, MSMEs lack of resilience and flexibility due to several things, such as the low level of digitalization, difficulties in accessing technology and a lack of understanding strategies to survive in business.So to overcome this challenge, MSMEs need to make accurate plans and strategies, so that companies can find out their strengths and weaknesses as well as opportunities and threats.SWOT analysis is used to obtain information derived from the analysis of the company's internal and external environmental situations.This analysis is needed to help develop MSMEs in recognizing their strengths and weaknesses as well as taking advantage of every existing opportunity and avoiding or minimizing threats in market competition.This research uses SWOT and TOPSIS analysis methods. SWOT analysis begins by weighting and ranking internal factors and external factors of MSMEs. The TOPSIS method is used to sort priorities from alternatives to the selected strategy.The results show that alternative strategies that can be applied are to create innovative new products, expand sales areas, increase promotions, turn business processes digital by using existing online platforms and expanding sales areas.